Brain imaging of vesicular monoamine transporter type 2 in healthy aging subjects by 18F-FP-(+)-DTBZ PET. - Kun-Ju Lin (Public Library of Science (PLoS), 2013)
Unlabelled (18)F-FP-(+)-DTBZ is a novel PET radiotracer targeting vesicular monoamine transporter type 2 (VMAT2). The goal was to explore the image features in normal human brains with (18)F-FP-(+)-DTBZ as a reference of molecular landmark for clinical diagnosis in Parkinson's disease (PD) and related disorders. Materials and methods A total of 22 healthy subjects (59.3±6.0 years old) including 7 men and 15 women were recruited for MRI and (18)F-FP-(+)-DTBZ PET scans. A total number of 55 brain VOIs were selected for quantitation analysis. The regional specific uptake ratio (SUR) was calculated with occipital as reference from MRI-based spatially normalized (18)F-FP-(+)-DTBZ images. Regional percentage SUR to that of anterior putamen was calculated. Average SUR images were displayed in 2D and 3D space to illustrate the image patterns. The correlation between age and regional VMAT2 uptake was also examined. Results Visual assessment showed symmetric uptake of (18)F-FP-(+)-DTBZ and obviously highest in striatum, followed by nucleus accumbens, hypothalamus, substantia nigra, and raphe nuclei. Quantification analysis revealed striatal VMAT2 density of anterior putamen>posterior putamen>caudate nucleus. Other subcortical regions were with moderate VMAT2 distribution (6∼51% SUR of anterior putamen), while slightly lower VMAT2 was observed in cerebellum (10.60% SUR) and much lower in neocortex (<5% SUR). No significant correlation of SUR to age was found in subcortical regions. Conclusion Using (18)F-FP-(+)-DTBZ PET, we showed the 2D and 3D imaging features of the VMAT2 distribution in vivo in healthy aging brains. The in vivo imaging characteristics of VMAT2 is consistent with the expression of VMAT2 in a recent autopsy study. Therefore, 3D visualization and higher image quality of (18)F-FP-(+)-DTBZ PET imaging might potentially be a powerful biomarker in detecting VMAT2 distribution of subcortical regions, and for Parkinson's disease and related neuropsychiatric disorders involving related monoaminergic systems.